User satisfaction on i-learn as Learning Management System (LMS) among UiTM Segamat degree student / Nurhidayah Mohd Razi ... [et al.] - Mohd Razi, Nurhidayah; Azahari, Muhammad Zahir Reza; Jusoh, Muhammad Kamil; Abu Khanifah, Muhammad Faris (2014)
This research is undertaken to study and identify the user satisfaction towards the usage of i-learn as learning management system implemented by UiTM among the UiTM Segamat degree students. In order to identify the user satisfaction, researcher is following the End User Computing Satisfaction (EUCS) model develops by Doll and Torkzadeh (1988). This model consists of 5 factors with 12 instruments. However, based on the literature on this area, researcher think that aside from the 5 factors of the EUCS model, it is wise to modified the existing model by adding two more new attributes to the model which are; organizational support and user's characteristics. This new attributes will then modified the model from 5 factors into 7 factors. A questionnaire was distributed among the UiTM Segamat Degree students in order to get the data for this research. This study reveals that the most influential factors that leads to user satisfaction is the content of the system and the EUCS models had correlation to the user satisfaction as the factors in the model will effects the user satisfaction. The results of this study can be used by UiTM Segamat for improvising and upgrading their learning management system following the factors the will generate and improve user satisfaction in order to facilitate the usage of the i-learn system among its users.